(untitled) (Conferencea, 2022)
The article emphasizes the following. Origin of Taxes, Concept and Importance of Taxes, Subject, Method and Sources of Tax Law, Tax History and Budget Relations in Periodic Periods Comparative Analysis, Tax Models and Their Signs in Developed Countries, Features of World Tax System Models, Comparative Analysis of the Tax System of the Republic of Uzbekistan with Models of the World Tax System, Comparative Analysis of the Tax System in the USA and the Tax System of the Republic of Uzbekistan, in Germany comparative analysis of the tax system and the tax system of the Republic of Uzbekistan, comparative analysis of the tax system of France and the tax system of the Republic of Uzbekistan.